Carotenoids produced by the deep-sea bacterium Erythrobacter citreus LAMA 915: detection and proposal of their biosynthetic pathway - Niero, Henrique; da Silva, Marcus Adonai Castro; de Felicio, Rafael; Trivella, Daniela Barretto Barbosa; Lima, André Oliveira de Souza (Folia microbiologica, 2021)
Technologies based on synthetic biology to produce bacterial natural carotenoids depend on information regarding their biosynthesis. Although the biosynthetic pathway of common carotenoids is known, there are carotenoids whose pathways are not completely described. This work aimed to mine the genome of the deep-sea bacterium Erythrobacter citreus LAMA 915, an uncommon bacterium that forms yellow colonies under cultivation. This work further explores the potential application of the carotenoids found and low-cost substrates for bacterial growth. A combined approach of genome mining and untargeted metabolomics analysis was applied. The carotenoid erythroxanthin sulfate was detected in E. citreus LAMA 915 cell extract. A proposal for carotenoid biosynthesis by this bacterium is provided, involving the genes crtBIYZWG. These are responsible for the biosynthesis of carotenoids from the zeaxanthin pathway and their 2,2'-hydroxylated derivatives. E. citreus LAMA 915 extracts showed antioxidant and sun protection effects. Based on the high content of proteases and lipases, it was possible to rationally select substrates for bacterial growth, with residual oil from fish processing the best low-cost substrate selected. This work advances in the understanding of carotenoid biosynthesis and provides a genetic basis that can be further explored as a biotechnological route for carotenoid production.
Keywords: Biosynthetic Pathways; Carotenoids; Sphingomonadaceae; biosyntetické dráhy; karotenoidy